Price Effects of Preferential Market Access: The Caribbean Basin Initiative and the Apparel Sector - Özden, Çaglar (World Bank, Washington, D.C., 2013)
Preferential trade arrangements should be evaluated by analyzing their effect on prices, rather than the total value of trade, as emphasized in the theoretical literature but rarely implemented empirically. The authors analyze the impact of the unilateral preferences granted by the U.S. Caribbean Basin Initiative (CBI) on the prices received by eligible apparel exporters. They use fixed effects generalized least squares (GLS) estimation to isolate the effects of various other factors (such as quality, exchange rates, and transactions costs) and identify the effects of tariff preferences. The authors find that CBI exporters only capture around two-thirds of their preference margin, despite the fairly competitive nature of the apparel market. This translates into a 9 percent increase in the relative prices they receive, but these numbers vary across countries and years. Countries specializing in higher-value items capture more of the preference margin while implementation of the North American Free Trade Agreement has a negative effect. The authors analyze the effect of Multi-Fibre Agreement (MFA) quotas imposed on third countries (such as China) and find that the benefits of CBI preferences will be significantly reduced once the quotas are fully removed in 2005.